A Multi‐Addressable Switch Based on the Dimethyldihydropyrene Photochrome with Remarkable Proton‐Triggered Photo‐opening Efficiency. Issue 1 (30th October 2014) - Roldan, Diego; Cobo, Saioa; Lafolet, Frédéric; Vilà, Neus; Bochot, Constance; Bucher, Christophe; Saint‐Aman, Eric; Boggio‐Pasqua, Martial; Garavelli, Marco; Royal, Guy
Abstract A series of photochromic derivatives based on the trans‐10b, 10c‐dimethyl‐10b, 10c‐dihydropyrene (DHP, "closed form") skeleton has been synthesized and their photoisomerization leading to the corresponding cyclophanediene (CPD, "open form") isomers has been investigated by UV/Vis and 1H NMR spectroscopies. Substitution of the DHP core with electron‐withdrawing pyridinium groups was found to have major effects on the photoisomerization efficiency, the most remarkable examples being to enhance the quantum yield of the opening reaction and to allow fast and quantitative conversions at much lower radiant energies. This effect was rationalized by theoretical calculations. We also show that the reverse reaction, that is, going from the open form to the closed form, can be electrochemically triggered by oxidation of the CPD unit and that the photo‐opening properties of pyridine‐substituted DHPs can be efficiently tuned by protonation, the system behaving as a multi‐addressable molecular switch. These multi‐addressable photochromes show promise for the development of responsive materials.